2016
DOI: 10.1371/journal.pone.0164408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cryopreserved Amniotic Membrane Orientation on the Expression of Limbal Mesenchymal and Epithelial Stem Cell Markers in Prolonged Limbal Explant Cultures

Abstract: PurposeTo evaluate the effect of prolonged limbal explants cultured without any scaffolds or on amniotic membrane (AM) on the viability, proliferation and differentiation potential of putative phenotypically defined cultured limbal mesenchymal (LMSC) and epithelial stem cells (LESC).MethodsLimbal explants were cultivated on cryopreserved intact AM or plastic plates using medium supplemented with only human serum. AM was positioned with either the epithelial or stromal side up. The outgrowing cells were immunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…LEGEND Screen analysis confirmed high expression of the commonly cited limbal epithelial cell markers: EGFR (88.81 ± 6.02) , SSEA‐4 (54.02% ± 5.93%) , CD71 (88.76 ± 5.92) , integrin β5 (91.45 ± 1.24) , integrin α6 (92.54 ± 6.41) , E‐cadherin (88.48 ± 6.06) as well as many other general markers of corneal epithelium. The presence of other markers previously related to limbal epithelial cells was also confirmed: CD40 (26.00 ± 6.94) , CD117 (c‐kit) (8.22 ± 2.56) , CD146 (67.04 ± 2.87), and CD166 (95.08 ± 0.97) as well as the presence of putative LSC marker integrin α9/β1 (4.85 ± 1.98) . The expression of the autophagy marker LAMP1 (84.82 ± 11.89) was also high, corroborating with previously reported data on limbal epithelial cultures .…”
Section: Resultssupporting
confidence: 65%
“…LEGEND Screen analysis confirmed high expression of the commonly cited limbal epithelial cell markers: EGFR (88.81 ± 6.02) , SSEA‐4 (54.02% ± 5.93%) , CD71 (88.76 ± 5.92) , integrin β5 (91.45 ± 1.24) , integrin α6 (92.54 ± 6.41) , E‐cadherin (88.48 ± 6.06) as well as many other general markers of corneal epithelium. The presence of other markers previously related to limbal epithelial cells was also confirmed: CD40 (26.00 ± 6.94) , CD117 (c‐kit) (8.22 ± 2.56) , CD146 (67.04 ± 2.87), and CD166 (95.08 ± 0.97) as well as the presence of putative LSC marker integrin α9/β1 (4.85 ± 1.98) . The expression of the autophagy marker LAMP1 (84.82 ± 11.89) was also high, corroborating with previously reported data on limbal epithelial cultures .…”
Section: Resultssupporting
confidence: 65%
“…Different populations of stem cells have been detected in human corneal tissue . Recently, MSC was also isolated from human cornea and found to play role in injury/wound healing process within the tissue . Luznic et al.…”
Section: Technical Highlights Of Explant Isolation Methods For Human Mscsmentioning
confidence: 98%
“…explanted limbal rim pieces including the epithelium as well as some of the superficial limbal stromal tissue. They detected two distinct population of stem cells after long‐term culture (when explants were cultivated for over 30 days) and found that after a second 30‐day explantation of same pieces into another dish, MSC population became 2‐fold in number . In another study, Vereb et al.…”
Section: Technical Highlights Of Explant Isolation Methods For Human Mscsmentioning
confidence: 99%
“…) and were performed as recently described (Lužnik et al. ). In brief, the remaining limbal rim was cut into approximately 1 × 2 × 0.25 mm equal pieces of limbal explants (biopsy), obtaining 5–6 limbal explants from each donor.…”
Section: Methodsmentioning
confidence: 99%